Rape in World War II film: comparing narrations - Dzadevych, Tetyana (Plural: History, Culture, Society, 2016)
The objective of this paper is to show how the filmmaker’s genre of choice shapes the main discourse of the film. The author compares Helke Sander’s documentary Liberators Take Liberties (1991-1992) and Max Farberbock’s narrative feature A Woman in Berlin (2008) both dealing with the dramatic effect of the end of WWII, in particular with the instances of German women having been raped by the Allied troops, a theme first publicized in the anonymous diary A Woman in Berlin (1953). There is a clear connection between the book and the two films, but if Sander focuses on the rape itself and on the extraordinary female experience of war, Farberbock is more concerned with cross-national revenge. The author looks closer at the genre elements, particularly at the genres of the diary, the (feminist) documentary, and the narrative film. Then, the author draws some parallels between the Helke Sander film and the diary A Woman of Berlin and discusses the documentaries within the feminist framework inspired by Sander’s accomplishments.